Sensitization and chronic beryllium disease at a primary manufacturing facility, part 1: historical exposure reconstruction - M Abbas Virji; Ji Young Park; Aleksandr B Stefaniak; Marcia L Stanton; Gregory A Day; Michael S Kent; Kathleen Kreiss; Christine R Schuler (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: Previous epidemiologic studies of beryllium sensitization (BeS) and chronic beryllium disease (CBD) have reported inconsistent exposure-response relationships, likely due to exposure misclassification. The objective of this study was to develop historical estimates of size-selective personal exposure to beryllium for an epidemiologic study. METHODS: In 1999, a cross-sectional survey of workers hired after 1 January 1994 was conducted at a beryllium production facility. Personal exposure data from two air sampling surveys conducted in 1999 were used to obtain total, respirable, and submicron particle baseline exposure estimates (BEE) for a job-exposure matrix (JEM). General area air samples collected from 1994-1999 were used to estimate annual changes in exposures (temporal factors) for 24 different process areas. Historical exposure estimates (HEE) were calculated by applying the temporal factors to the BEE. Workers were assigned HEE based on their work history, and their historical exposure profile was summarized as cumulative, average, or highest-ever job exposure. RESULTS: Changes in exposure over a 6-year period were observed in 10 of the 24 process areas with an overall mean decline of 18% per year. The overall total exposure for study participants over their work tenure ranged from: 0.001-34.44 μg/m^3-year, 0.01-16.26 μg/m^3, and 0.01-17.54 μg /m^3 for cumulative, average, and highest-ever job, respectively. For respirable exposures, the ranges were: 0.001-15.54 μg/m^3-year, 0.01-3.56 μg/m^3, 0.01-5.54 μg /m^3 for cumulative, average, and highest-ever job, respectively. CONCLUSIONS: Using this JEM, exposure-response relationships for BeS and CBD can be explored over a range of exposure metrics such as total, respirable, and submicron beryllium mass concentrations, including summary measures such as cumulative, average, or highest exposures, with the ultimate objective of elucidating a quantitative exposure-response relationship.